Beyond Barriers: Optimizing Legal Protection and Inclusive Business Policies for Disability Participation - Deswari, Meissy Putri; Eldiva, Fiyola Triana; Ridha Annisa (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
This research primarily aims to answer the question of how the optimization of legal protection and inclusive business policy models can strengthen the participation of persons with disabilities in the business world in Indonesia. Although a legal framework is available, the participation of persons with disabilities in formal employment remains low, indicating a gap between the legal norm and its implementation.The study employs a qualitative approach using policy analysis and empirical law to identify implementation barriers and formulate solutions based on a collaborative model. The findings indicate that most companies still view inclusive policies as an administrative obligation rather than a sustainable business strategy. Based on these findings, the Three-Pillar Inclusive Business Policy Model was developed : Regulation and Incentives, Internal Corporate Transformation, and Collaboration and Inclusive Capacity. This model integrates the roles of the government, the business sector, and disabled persons' organizations. This model introduces novelty in its inclusive governance approach, which emphasizes the synergy between law and corporate practice to strengthen the inclusive employment ecosystem. The implication is that this policy will not only enhance the effectiveness of the law and corporate compliance but also reinforce social justice and national economic contribution through increased participation of the disabled workforce. Therefore, employment inclusivity must be viewed as a strategic investment toward fair, sustainable, and humanitarian-value-oriented development.